Age and Sex: The Demographic Factors Matter in Sight Care Treatment Decision in Nepal - Bhusal, Durga (Butwal Campus Journal, 2022)
Even though existing philosophy advocating patients should be active partakers in treatment decision-making about their care, the literature suggests that patients require be informing but not involving. Eyesight treatment-decision of the participants involving free Eye-Care-Camp in a one-day free Eye-Care-Camp organized by Krim Samaj with the technical support of Tamnagar Chasma Ghar were considered with 91 responses. Two technical officers checked up the eye conditions. On the Treatment Decision-Making, they overwhelmingly wished to be performed by the technical officers. Near and free service was a most influencing factor for the treatment decision. Age significant result regarding eyesight care treatment-decision was appeared in the study. Although the treatment decisions of patients were autonomous up to the participation in free eye care camp, few wishes to hand over the treatment decision-making control to their technical personalities. The findings suggested that choices are not free but controlled under the technical officer, and household decision. Hidden serious eye problems not exhibited in household got the chance to disclose and the patients got the idea what to do further.